2014
DOI: 10.1021/ic500050q
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CO2 Reduction in N,N-Dimethylacetamide/Water as an Alternative Solvent System

Abstract: N,N-Dimethylacetamide (DMA) was used for the first time as the reaction solvent in the photocatalytic reduction of CO2. DMA is highly stable against hydrolysis and does not produce formate even if it is hydrolyzed. We report the catalytic activities of [Ru(bpy)2(CO)2](PF6)2 (bpy = 2,2'-bipyridine) in the presence of [Ru(bpy)3](PF6)2 as a photosensitizer and 1-benzyl-1,4-dihydronicotinamide (BNAH) as an electron donor in DMA/water. In the photochemical CO2 reduction, carbon monoxide (CO) and formate are catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 39 publications
4
110
0
1
Order By: Relevance
“…We further showed that the oxidized form of BNAH was the BNA dimer, e.g. , 1,1′-dibenzyl-1,1′,4,4′-tetrahydro-4,4′-binicotinamide (4,4′-BNA 2 ), 47,49 indicating that the reduced species of the photosensitizer ([Ru(bpy) 3 ] + ), which was generated by the reductive quenching of the excited [Ru(bpy) 3 ] 2+ with BNAH, supplied the electrons to the catalyst.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…We further showed that the oxidized form of BNAH was the BNA dimer, e.g. , 1,1′-dibenzyl-1,1′,4,4′-tetrahydro-4,4′-binicotinamide (4,4′-BNA 2 ), 47,49 indicating that the reduced species of the photosensitizer ([Ru(bpy) 3 ] + ), which was generated by the reductive quenching of the excited [Ru(bpy) 3 ] 2+ with BNAH, supplied the electrons to the catalyst.…”
Section: Introductionmentioning
confidence: 90%
“…14 Until now, many metal complexes have been investigated for CO 2 reduction catalysis. 515 As metal complexes for the catalysts, manganese mono(bipyridyl) tricarbonyl, 1618 cobalt and iron porphyrin, 1921 cobalt tris(bipyridyl) 22 and macrocycle, 23,24 nickel cyclam, 2527 molybdenum and tungsten mono(bipyridyl) tetracarbonyl, 28 rhodium bis(bipyridyl), 29,30 palladium phosphine, 3133 rhenium mono(bipyridyl) tricarbonyl, 3442 osmium mono(bipyridyl) dicarbonyl, 43,44 iridium poly(pyridyl) and dihydride pincer, 45,46 ruthenium mono(bipyridyl) and bis(bipyridyl) dicarbonyl complexes 4770 have been investigated. Most of these yield CO and/or formate as the two-electron reduction products of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O CO 2 pode ser reduzido diretamente em superfícies metálicas, entretanto, o sobrepotencial ainda é extremamente alto e ocorre o envenenamento da superfície do metal. [198][199][200] Desta maneira, o uso de compostos de coordenação como fotocatalisadores ou eletrocatalisadores é a vanguarda destas reações, [201][202][203][204][205][206] pois nestes compostos pode-se ajustar seus potenciais formais de redução de maneira a corresponder aos potenciais necessários para redução de CO 2 , assim como também podem favorecer a cinética e aumentar a estabilidade do estado de transição, o que torna a catálise altamente modulável. 207 O mecanismo genérico para a redução de CO 2 fotoassistida por complexos metálicos inicia-se em um composto de coordenação atuando como fotossensibilizador, F, que é excitado, F*, após absorver luz, Equação 4.…”
Section: Conversão De Luz Em Energia Químicaunclassified